Relationship between the Level of Amylinemia and Albuminuria Categories in Patients with Latent Autoimmune Diabetes in Adults - Tsaryk, Iryna; Pashkovska, Nataliia (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: β-cells of islets of Langerhans produce not only insulin but another hormone – amylin, whose role in the development and progression of chronic kidney disease (CKD) in patients with diabetes mellitus (DM) is not known for certain. AIM: The aim of the study was to determine the relationship between amylinemia and albuminuria categories in patients with latent autoimmune diabetes in adults (LADA) and CKD. METHODS: 89 patients with DM and CKD were examined, as well as 15 representatives of the control group. The patients were divided into three groups by the types of DM: 36 patients with LADA, 25 patients with classical type 1 diabetes mellitus (T1D), and 28 patients with type 2 diabetes (T2D). Serum amylin levels were measured using the enzyme-linked immunosorbent assay (ELISA) method. RESULTS: In the group of patients with LADA, the amylin content was 9.0 times higher than in control (p < 0.01) and 6.8 times higher compared to classical T1D (p < 0.01); at the same time, it was 17.3% lower than in T2D group (p < 0.05). In patients with T1D, the level of amylinemia did not change, whereas in T2D group it was 10.8 times significantly higher compared to the control and 8.3 times higher than in the group of patients with classical T1D. The highest indicator was registered in patients with LADA2 phenotype. The level of amylin was increasing in proportion to the categories of albuminuria. Positive correlations were found between the content of amylin and insulin, C-peptide, Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) index and creatinine. CONCLUSION: Serum amylin level significantly increases progrediently to the albuminuria categories in patients with LADA (especially in LADA2 phenotype) and T2D.